Online Analytical Processing (OLAP) for Disaster Report - Kadek Ary Budi Permana; Dewa Ayu Putri Wulandari; Putu Arya Mertasana (International Journal of Engineering and Emerging Technology, 2018)
Data analysis of disaster is very important forsupporting in making decision to cope with the next disaster orprepare if the disaster will happen again. Online AnalyticalProcessing (OLAP) becomes solution to get analysis by usingcertain analysis that supplied in OLAP. To supply the dataanalysis in which done by OLAP so the data as the representativein multidimensional model that manages the data in cube form.Warehouse data can be called as the place from source data thatused to make easier in analysis information process in it becauseconcept of data dimensional offered. The planning data warehouseis basically by source data that gotten and decided by thedescription of needs from the users. OLAP in this disaster reportsuccess in implementation with helping data warehouse and implysnowflake schema to dimensional data first.